Single-Row Transformation of Trees into Single-Row Networks - Loh, Ser Lee; Salleh, Shaharuddin; Sarmin, Nor Haniza (2009)
A tree is a connected graph where any two distinct vertices are connected by exactly one path. A tree has no cycle and there exists only one root node. Many engineering and science problems in our real life which involve the transferring of information can be represented or reduced into a tree and solved through its single-row representation. In this paper, we will present a model which transforms a tree into a single-row network, namely Tree Sequence Modeling (TSM). This model contains the formation of zones, terminals and intervals where Formation of Zones involves the Formation of Partition and Insertion Mechanisms. The single-row network formed by TSM is then solved using ESSR. Experimental result shows TSM can transform all kinds of trees into the single-row network efficiently.